(untitled) (Comparative & International Education Series, 2024)
With a focus on teaching and learning, this chapter seeks to examine the impact and implications of ChatGPT and AI technologies in higher education. By evaluating strategies and practices for preparing educators and students to effectively utilize ChatGPT and AI technology for academic and professional success, the aim is to offer policy recommendations. Guided by the pedagogical dimensions of the AI Ecological Education Policy Framework (Chan, 2023), this systematic review synthesizes previous literature in four areas: assessments and examinations, student competencies, AI-driven workplace, and a balanced approach to AI adoption. By identifying best practices across these areas and offering recommendations to enhance ethical and effective implementations of AI technology, this study contributes to the existing literature on AI technology-related policies in higher education. The chapter intends to assist educators and students in higher education in navigating the challenges and opportunities presented by advanced AI technologies and ChatGPT.